Heirs of the Apostles : Studies on Arabic Christianity in Honor of Sidney H. Griffith - Bertaina, David; Keating, Sandra Toenies; Swanson, Mark; Treiger, Alexander; Griffith, Sidney Harrison (Arabic Christianity, 2019)
Heirs of the Apostles offers a panoramic survey of Arabic-speaking Christians-descendants of the Christian communities established in the Middle East by the apostles-and their history, religion, and culture in the early Islamic and medieval periods. The subjects range from Arabic translations of the Bible, to the status of Christians in the Muslim-governed lands, Muslim-Christian polemic, and Christian-Muslim and Christian-Jewish relations. The volume is offered as a Festschrift to Sidney H. Griffith, the doyen of Christian Arabic Studies in North America, on his eightieth birthday. Contributors are: David Bertaina, Elie Dannaoui, Stephen Davis, Nathan P. Gibson, Cornelia Horn, Sandra Toenies Keating, Juan Pedro Monferrer-Sala, Johannes Pahlitzsch, Andrew Platt, Thomas W. Ricks, Barbara Roggema, Harald Suermann, Mark N. Swanson, Shawqi Talia, Jack Tannous, David Thomas, Jennifer Tobkin, Alexander Treiger, Ronny Vollandt, Clare Wilde, and Jason Zaborowski.